A statistical, epidemiological and financial health approach to the retail trade sector in Colombia (2012)
A combined model of health, risk and financial analysis was applied to the economic sector of retail trade. The financial statements of 2238 companies, in Colombia, were sorted out into healthy and sick clusters, by items of cash at end of period, profit and loss and equity, in a cluster analysis. A cutoff point for the items of the financial statements to discriminate between healthy and sick companies was computed. Based on the dichotomous categories of sick/healthy company and over/under cutoff point for each item, odds ratio and relative risk for financial health, were calculated. Finally, acid test, working capital, current assets, indebtedness, concentration of indebtedness and leverage ratios were computed using the risk factors for the whole sector.